PENGARUH MODEL PEMBELAJARAN GENERATIF UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS III - Roni Hamdani, Acep; Nurpajarina, Wina (STKIP Subang, 2021)
This study aims to determine the effect of the generative learning model to improve the mathematical connection of elementary school students. This research was conducted at SDN Tanjungwangi in the 2020/2021 academic year with a research sample of 20 class III A students and 20 class III B students. This research method uses a quasi-experimental method. The data analysis technique in this study uses N-gain calculations to measure the increase in students' mathematical connection abilities, (t-test) to determine the effect of using generative learning models on students' mathematical connection abilities. The results showed that (1) an increase in mathematical connection ability with an average N-gain in the experimental class obtained a result of 0.79 with the criteria